Kajian Pengaruh Material Graphene pada kinerja Biosensor Berbasis Surface Plasmon Resonance (SPR) pada Deteksi Makanan Halal sebagai Pendukung Halal Research Center UIN Sunan Kalijaga Yogyakarta - Wida Yanti; Asih Melati (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2017)
Halal foods and medicines are an absolute daily needs for the Muslim community in Indonesia. Therefore the authority institutions in indonesian goverment should ensure the availability of this. It is of course inseparable from the role of higher education through the development of its technology to develop halal detection of foods and drugs. This study is an effort to contribute to the Halal Research Center of UIN Sunan Kalijaga Yogyakarta through the biosensor development in halal detection foods and medicines based on biosensor SPR. This device using graphene materials to improve the detection sensitivity of pork gelatin material that is likely contained in foodstuffs and medicine. From analytical calculation and computation, enhancement of the SPR biosensor performance by involvement graphene it was shown through the ATR (Attenuated Total Reflectance) reflective curve. The result of this results was found the enhancement of the sensitivity 2,86 %.Keyword: Surface Plasmon Resonance (SPR), Porcine Gelatin, Graphene, ATR